Effective inclusive teacher education for special educational needs and disabilities: Some more thoughts on the way forward. (January 2017) - Robinson, Deborah
Abstract: This study sought to identify the principles and practices underpinning effective inclusive teacher education for special educational needs (SEN) in ordinary schools through an inclusive action research project. The findings demonstrate that where practitioner development involves critical-theoretical, reflexive, research-oriented collaborations among a professional learning community, practitioners become more confident and skilful in enacting inclusive practice. This community was formed in the context of a school-university partnership and included pre-service teachers, experienced teachers, teaching assistants and university tutors. Its findings cast serious doubt over the efficacy of de-intellectualised, 'on the job' training models favoured by policy makers in England and elsewhere. Highlights: How some models of inclusive teacher education for special educational needs fail. Practices and principles underpinning efficacious inclusive teacher education. The findings of an inclusive action research project. The evidence base for effective inclusive teacher education. Recommendations for teacher educators about ways forward.